MRI: an insight - Tim Peter; Deepthi Cherian (Wolters Kluwer Medknow Publications, 2018)
MRI has been a potential tool for lesion diagnostics in the human body. It is accurate owing to the sound biological principle behind it. It has an array of unique features but is not free from certain constraints that hinder the smooth progression of its course. This article throws light on the salient features and constraints pertaining to MRI, with an insight towards the future prospects of the same.